Transplantation of Human Retinal Pigment Epithelium Cells in the Treatment for Parkinson Disease - Yin, Feng (CNS Neurosci Ther, 2012)
BACKGROUND AND PURPOSE: To assess the clinical effect of transplantation of human retinal pigment epithelial (hRPE) cells into the unilateral postcommissural putamen for treatment for Parkinson disease (PD). METHODS AND RESULTS: Cells from postmortem human eye tissue (10–20 weeks of gestation) were cultured in vitro. Cells from ‐generation passage were implanted in PD postcommissural putamen with stereotactic operation in 12 patients with PD. All patients tolerated surgery well, and no major adverse events occurred. Eleven patients showed improvement in the primary outcome measure at 3 months post‐treatment, particularly the Unified Parkinson's Disease Rating Scale‐M score in the off state. Response reached a peak at 12 months and declined during the next 24 months. At the 36‐month endpoint, there were eight patients who felt better than at baseline. Positron emission tomography (PET) showed a trend with increased dopamine (DA) release during the first 6 months. CONCLUSION: Human retinal pigment epithelial cells have the characteristics of neural progenitor cells and can be induced to differentiate into DA neurons. The results of this clinical trial suggest that the treatment of transplanted hRPE cells could improve symptoms of PD. These cells might serve as a useful source of DA neurons for neural graft in the treatment for PD.